INTRINSIC AND EXTRINSIC ELEMENTS OF VOVA SANGGAYU FOLKLORE IN PASANGKAYU REGION - Marlina Marlina; Ulinsa Ulinsa; Ade Nurul Izatti; Aurelia Vila (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Intrinsic and Extrinsic Elements of Vova Sanggayu Folklore In Pasangkayu Region. Focus in this research is : How intrinsic and extrinsic structure of oral literature in Vova Sanggayu folklore? This research aimed to describe the intrinsic and extrinsic structure of oral literature in Vova Sanggayu folklore. This research is a descriptive qualitative research, this methode describe intrinsic and extrinsic structure of oral literature in Vova Sanggayu folklore. The data in this research is written data from the folklore text about the origin of Pasangkayu Region name (Vova Sanggayu folklore). The data collecting conducted by observation, interview, recording, documentation, evaluation technique. Based on this research reveals the building elements in Vova Sanggayu folklore, involving : (1) intrinsic elements consist of theme, plot, characters and characterizations, setting, point of view, style, message and (2) extrinsic element in folklore consist of biography, social values, religion values, cultural values, moral values.